Unlocking Potential Overcoming Educational Challenges through Leadership in Qatar; A Thematic Analysis-Based Approach - Al-Kubaisi, Huda; Shahbal, Sayed (Journal of Ecohumanism, 2024)
Background: Qatar’s ambitious vision of becoming a knowledge economy necessitates a robust education system. However, persistent challenges such as students’ socioeconomic disparities, gender inequality, and language barriers impede educational progress. Addressing these barriers requires effective leadership strategies within the educational administration. Aim: This qualitative study aims to investigate the educational barriers and challenges in Qatar’s schools and propose leadership solutions to overcome them. By exploring the perspectives of teachers, it seeks to identify key challenges and inform leadership approaches that enhance the accessibility and quality of education in schools. Method: An inductive thematic analysis approach was employed, involving semi-structured interviews with experienced school teachers (N=10) to achieve the main aim of the study. Data collection and analysis were conducted systematically using qualitative data analysis software to identify emergent themes and provide insights into the challenges of educational administration and potential solutions. Findings and Results: The analysis revealed significant challenges in Qatar’s education system, particularly schools, including the impact of students’ socioeconomic status, gender inequality, language barriers, and inadequate support for special needs. However, the potential for leadership initiatives to address these challenges and improve educational outcomes was evident. Conclusion: Effective educational leadership in Qatari schools is crucial for overcoming barriers and fostering a conducive learning environment for all students. By implementing targeted interventions, promoting inclusive practices, and collaborating with stakeholders, educational administrators, i.e. school leadership, can drive positive change and unlock the nation’s educational potential.